Tribology in Malaysia: General perspective - Abdollah, Mohd Fadzli bin (2016)
Tribology was first coined in 1966 as documented in ‘Jost Report’. The word ‘tribology’ has since gained a common usage for matters related to friction, wear, and lubrication in machine in-teractions. Since tribology is an engineering issue that goes beyond national boundaries, many tribology societies have emerged across the continents partly motivated by the pursuit for green-er world via waste reduction. The move for improved tribology practices in industry has reached Malaysia and in 2007, Malaysian Tribology Society (MYTRIBOS) was established by local tribol-ogists [1]. MYTRIBOS is responsible to promote proper practices in research and development related to the field of tribology in Malaysia and to facilitate collaborations between academia and industry in all possible endeavors. MYTRIBOS eventual vision and mission is to help reduce en-ergy consumption by making machineries more energy efficient in order to reduce greenhouse gas emission. MYTRIBOS is contributing towards the improvement of the environment and to achieve a better quality of life and more sustainable world by creating awareness of the impor-tance of practicing proper tribology.